T–cell Acute Lymphoblastic Leukemia in a Patient with Pre–existing Essential Thrombocythemia: A Case Report and Literature Review. (2021) - Medawar, Georgio; Ackula, Haritha; Weinberg, Olga; Roberts, Todd; Meleveedu, Kapil
Abstract: The occurrence of T–cell acute lymphoblastic leukemia (T–ALL), on a background of preexisting Philadelphia–negative Myeloproliferative neoplasm is rare. Among the few reported cases where no deep molecular sequencing was performed, it was difficult to ascertain whether these leukemia's occurred de-novo or were due to the clonal progression of underlying MPN. We present a case of a 49–year-old man with a history of essential thrombocythemia who subsequently developed T–ALL. By utilizing next generation sequencing we were able to determine that these two entities originated from two distinct clones and were likely random events. We report the outcome and review the literature.